The Effect of Teacher Competence and Self-Efficiency on Teacher Performance With Transformational Leadership of the Head of School as a Moderating Variable in Senior High School Tangerang Regency - Thomas Reggiani Alfredo; Budi Prijanto (Dinasti International Journal of Management Science, 2022)
The main problem in this study is that some teachers do not show maximum performance. Many factors affect teacher performance, but in this study analyzed through competence, self-efficacy, and transformational leadership of the principal as moderating variables. The purpose of this study was to determine the effect of teacher competence and self-efficacy on teacher performance with the principal's transformational leadership as a moderating variable at senior high school Tangerang Regency. This research data is primary data, by distributing questionnaires to 94 public high school teachers in Tangerang Regency. Data were analyzed using Partial Least Square (PLS) program. The results of this study indicate that: (1) teacher competence affects teacher performance, (2) self-efficacy affects teacher performance, (3) principal transformational leadership weakens the influence of teacher competence on teacher performance, (4) principal transformational leadership strengthens the influence self-efficacy on teacher performance.